2018
DOI: 10.3390/cancers10120502
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pain in Cancer: Towards Personalised Medicine

Abstract: Despite increased attention to cancer pain, pain prevalence in patients with cancer has not improved over the last decade and one third of cancer patients on anticancer therapy and half of patients with advanced disease still suffer from moderate to severe pain. In this review, we explore the possible reasons for the ongoing high prevalence of cancer pain and discuss possible future directions for improvement in personalised pain management. Among possible reasons for the lack of improvement are: Barriers for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 71 publications
0
43
0
3
Order By: Relevance
“…Neuropathic cancer pain is associated with poor outcomes [7,8]. A study in 2012 found that neuropathic cancer pain was associated with more oncological treatment, greater analgesic requirements (including strong opioids and adjuvant analgesics) and reduced performance status than those with nociceptive pain [8].…”
Section: Definitions and Epidemiologymentioning
confidence: 99%
“…Neuropathic cancer pain is associated with poor outcomes [7,8]. A study in 2012 found that neuropathic cancer pain was associated with more oncological treatment, greater analgesic requirements (including strong opioids and adjuvant analgesics) and reduced performance status than those with nociceptive pain [8].…”
Section: Definitions and Epidemiologymentioning
confidence: 99%
“…Bone cancer pain (BCP) is often severe and intractable, and has a strong effect on the quality of life of cancer patients. But no breakthrough has been achieved yet with regard to the therapeutic strategies and mechanisms of BCP (Falk and Dickenson, 2014;van den Beuken-van Everdingen et al, 2018). Therefore, novel and more efficacious therapies are imperative to improve the quality life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…11 In fact, 40% of cancer patients have reported to experience pain in varying degrees. 12,13 A number of studies conducted in European countries and in other parts of the world also revealed similar results, 1416 however, inadequate pain management in cancer is indeed a current challenge in China. As far as we know, one of the problems is the regulation of opioid distribution and its accessibility for treatment purposes.…”
Section: Introductionmentioning
confidence: 67%